Biological control of a plant pathogen and pest by expression of a cloned Serratia marcescens chiA gene and Bacillus thuringiensis cryIA(c) gene in endophytic bacteria - Downing, Katrina Jo (Department of Molecular and Cell Biology, 2016)
Bibliography: pages 117-130.